Afghanistan in the Heart of Asia: Geopolitical Fragmentation, Climate-Induced Fragility, and the Future of Eurasian Connectivity - Sail, Ezat Ullah; Miakhil, Jan Mohammad (Multidisciplinary Journal of Education , Economic and Culture, 2026)
Central Asia is currently undergoing a profound transformation in regional cooperation, shifting from a passive geopolitical space to an active agent asserting itself through new connectivity initiatives and multisector diplomacy. However, the realization of a cohesive regional order is inextricably linked to Afghanistan's stability and integration. Despite its geographic centrality as the "Heart of Asia," Afghanistan remains a fragmented node, functioning more as a geopolitical barrier than a bridge within emerging regional connectivity corridors. This paper critically examines the multidimensional obstacles hindering Afghanistan's integration into the broader Central Asian regional architecture. Unlike traditional studies that focus predominantly on military security or terrorism, this research utilizes a geopolitical framework to analyze the intersection of border disputes—most notably the Durand Line conflict—and the influence of external power rivalries. Furthermore, the study investigates an under-researched dimension: how climate-induced resource scarcity exacerbates geopolitical fragility. It argues that sustainable connectivity initiatives, such as the Trans-Caspian and Middle Corridors, cannot realize their full economic potential without addressing Afghanistan's security vacuum and emerging environmental crisis. By assessing the potential of the "Heart of Asia" process, the study concludes that excluding Afghanistan from strategic planning perpetuates instability and proposes that future frameworks must adopt an inclusive approach, integrating Afghanistan’s economic potential with regional security imperatives to ensure long-term stability across Eurasia.